The impact of changes in financial and macroeconomic variables on term structure of interest rates in Malaysia - Ong, Tze San; Lai, Ngan Yoke; Teh, Boon Heng (Human Resource Management Academic Research Society, 2012)
Based on time series model, the connection between term structures of interest rate, financial and macroeconomic variables is explored for Malaysia from 1997Q1 to 2009Q2. The behavior of maturity spreads is examined in detail and regression model is established using Ordinary Least Square (OLS) method. The findings show that some macroeconomic variables do not have significant impact on maturity spreads. The money supply affect maturity spread positively while current account influence maturity spread negatively. The other variables, namely stock market return, gross domestic product, industrial production index, inflation rate and trade balance, have no relations with maturity spread. Future work should seek out the effects of maturity spreads on macroeconomic conditions.